Construção e reconstrução de novas formas sociais de vida nas colônias de hanseníase do Brasil - Estigma, segregação, violência e superação - Cordovil Neves de Souza (2021)
This work is a national study, qualitative, about the new ways of life and sociability constructed by people who were interned in leprosy colonies in the five Brazil’s regions. The research was organized from the methodological proposal of Grounded Theory, collected through semi-structured interviews with 15 (fifteen) people who were affected by hansen disease and compulsorily hospitalized; and documentary analysis of the literature produced by ex- inmates of these establishments in books and periodicals. Respecting the coding and analysis steps proposed by the Grounded Theory, the data were grouped into categories entitled: stigma, mortification, construction of new forms of sociability and hope. Based on their organization, the core category “Construction and Reconstruction of New Social Forms of Life in Hansen Colonies in Brazil” was identified, which gives the title to this dissertation. The constructed theory suggests that stigma was responsible for the millenary prejudice and exclusion that the people with Hansen disease was subjected to, a fact that resulted in segregationist and arbitrary public policies that had the support of society. The violence of compulsory internment destroyed the inmates’ subjectivity, seeking to erase his previous history in a process of mortification. Adapting to everyday life in the colonies was only possible through the construction of a collective experience for the inmates and their peers. Work, art, sport and religiosity were some of the instruments that facilitated adaptation, acceptance and the consequent subordination to incarceration, reducing confrontations with the imposed system and escapes. However, the resistance and struggle for rights and dignity were also always present in the histories of the colonies. Often, the process of being initiated into mortification, went through adaptation, almost always went through the resignification of life and history and resulted in the construction of a new consciousness. For many, supported by the collective struggle, this stage was based on recognition as subjects of rights in search of their full citizenship.